Activation, strength, and resistance: Which variables predict the kinematics of women with and without patellofemoral pain? - Morita, Ângela Kazue [UNESP]; Navega, Marcelo Tavella [UNESP] (Elsevier, 2023)
Introduction: Investigating the possible relationship between neuromuscular changes and movement alterations could help to describe the mechanisms underlying patellofemoral pain (PFP). Objective: To investigate whether activation and muscle strength of the trunk and lower limb and muscle resistance of the trunk predict the knee frontal and trunk sagittal kinematics in women with and without PFP. Method: Sixty women (PFP, n = 30; asymptomatic, n = 30) underwent the single-leg squat test to collect electromyographic and kinematic data. Activation of transversus abdominis/internal oblique, gluteus medius (GMed), and vastus medialis oblique (VMO); knee frontal and trunk sagittal angles were analyzed. Participants also underwent maximal isometric tests to determine lateral trunk, hip abductor, and knee extensor torques and performed a lateral trunk resistance test. Multiple regression was used to determine predictive models. Results: In the PFP group, knee frontal angle (R2 = 0.39, p = 0.001) was predicted by GMed activation (β = 0.23, p = 0.000) and hip abductor torque (β = 0.08, p = 0.022). No variable was able to predict trunk sagittal kinematics in this group. In the asymptomatics, knee frontal angle (R2 = 0.16, p = 0.029) was predicted by hip abductor torque (β = 0.07, p = 0.029), while trunk sagittal angle (R2 = 0.24, p = 0.024) was predicted by VMO activation (β = 0.12, p = 0.016). Conclusion: Kinematics is predicted by the muscles acting in the respective planes, such that hip abductors capacities are related to the knee frontal alignment in both groups, and that of the VMO is related to the trunk sagittal alignment only in asymptomatic women.
Keywords: Disability evaluation; Electromyography; Forecasting; Muscle strength